THE PROJECTION OF THE EDUCATIONAL AND PROFESSIONAL SPHERES‘ INFLUENCE ON THE FUTURE TEACHERS‘ PERSONALITY ORIENTED POSITION FORMATION - Chobitko, M. G. (Continuing Professional Education: Theory and Practice, 2019)
Our studies provide a basis to assert that the formation of studentteacher professional positions largely due to how organized learning environment in school. His humanistic orientation is determined by: the presence of reflexive and innovation environment in the educational system, the common design of the educational process of all its members, studentoriented approach to the educational process; atmosphere institutions, characterized by trust, openness, shared activities for students and teachers, cocreation, on yektyvizatsiyeyu in the pedagogical community personal values and meanings, the presence of feedback on the status, development status and problems of all members of the educational process; organization personal experience of living and working conditions of the participants of the educational process in freedom and responsibility, “living in the humanistic paradigm” (meetings, clubs, recreation, educational seminars); openness of the educational system, involving analysis of public examination as a means of humane support